SARANA PROMOSI MELALUI BROSUR DAN INSTAGRAM PADA PERPUSTAKAAN SEKRETARIAT DAERAH PROVINSI KALIMANTAN BARAT - Afriani, Aulia; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Library of West Kalimantan Provincial Secretariat is a special library of government agencies The Regional Secretariat Library has a complete collection of the 000-900 class but visitors who come to the library of Setda are less than 10 people per day. The purpose of this research is to know the importance of promotion for the library of Regional Secretariat as well as promotional facilities conducted by the Regional Secretariat Library and the constraints faced in the promotion process. In taking data for completeness of Final Project, writer use qualitative research method with descriptive approach which describes event based on data obtained through interview with informant. Data collection is done by direct observation in field, interview, and documentation. The interview was conducted with the Library Manager and Head of Subdivision and Library of. Promotion can be done with two means that is with the print media and social media to attract the public's attention. The printed form of brochures and social media is instagram.Â Keywords: Promotion Means, Library Setda, Brochures, Instagram.